RESISTANCE, RACE, AND MYTH: A CRITICAL SURVEY OF AMERICAN POPULAR MUSIC CULTURE IN THE 20TH CENTURY - Church, Scott Haden (Dialogue, 6(3), 2019)
The topic of popular music in the United States has garnered much analysis from scholars, particularly how popular music has created or reflected American myths, collective memory, and racial politics. This essay is a review of select research on the interface between 20th century American popular music, culture, and power. The essay reveals that pop music scholarship is rooted in paradox. Hence, it focuses on three chiastic or antithetical themes permeating scholarship on the topic: Popular music as either cultural hegemony or resistance to that cultural hegemony; Popular music as fundamental to the American myth, or the American myth as fundamental to popular music; and Popular music as inextricable from American race, or race as inextricable from American music. Further, it sheds light on the interconnectedness of American culture and popular music in the 20th century. This review of critical scholarship on popular music culture in the 20th century is significant for popular culture studies and pedagogy because it provides a frame of reference from which scholars and teachers may formulate research about popular music in the 21st century. Keywords: Popular Music, Race and Ethnicity, American Dream, Gender, Class, Postwar
Keywords: Type of access: Open Access